Highly sensitive Escherichia coli shear horizontal surface acoustic wave biosensor with silicon dioxide nanostructures - Ten, Seng Teik; Hashim, Uda; Gopinath, Subash C.B; Liu, W.W.; Foo, K.L.; Sam, S.T; Ab Rahman, Siti Fatimah; Voon, Chun Hong; Nordin, Anis Nurashikin (Elsevier Limited, 2017)
Surface acoustic wave mediated transductions have been widely used in the sensors and actuators applications. In this study, a shear horizontal surface acoustic wave (SHSAW) was used for the detection of food pathogenic Escherichia coli O157:H7 (E.coli O157:H7), a dangerous strain among 225 E. coli unique serotypes. A few cells of this bacterium are able to cause young children to be most vulnerable to serious complications. Presence of higher than 1 cfu E.coli O157:H7 in 25 g of food has been considered as a dangerous level. The SHSAW biosensor was fabricated on 64° YX LiNbO3 substrate. Its sensitivity was enhanced by depositing 130 nm thin layer of SiO2 nanostructures with particle size lesser than 70 nm. The nanostructures act both as a waveguide as well as a physical surface modification of the sensor prior to biomolecular immobilization. A specific DNA sequence from E. coli O157:H7 having 22 mers as an amine-terminated probe ssDNA was immobilized on the thin film sensing area through chemical functionalization [(CHO-(CH2)3-CHO) and APTES; NH2-(CH2)3-Si(OC2H5)3]. The high-performance of sensor was shown with the specific oligonucleotide tar- get and attained the sensitivity of 0.6439 nM/0.1 kHz and detection limit was down to 1.8 femto-molar (1.8×10−15 M). Further evidence was provided by specificity analysis using single mismatched and complementary oligonucleotide sequences.